Tourism Evaluation of Derawan Island through Gap Analysis Approach - Althalets, Fareis; Hetami, Adietya Arie; Aransyah, Muhammad Fikry; Aulia, Andi (Budapest International Research and Critics University, 2021)
The tourism potential of East Kalimantan is located in the Berau district, namely Derawan Island that offers charming marine tourism destinations and underwater parks that interest national and foreign tourists. The problem's urgency was collected from the field analysis results by observing, listening and interviewing all tourism actors on Derawan Island. From the results of identifying urgency or problems that occur as phenomena on Derawan Island, it will be the primary instrument in the GAP analysis, which becomes one of the methods to identify the right solution in creating recommendations for solving problems that occur on Derawan Island. The initial step considered in the development of ecotourism on Derawan Island is to determine a clear idea about the object that will be planned as an ecotourism object and strategies are used to develop it, as well as to conduct a feasibility study related to the weaknesses and strengths of the resources available in the area. To be used as the basis for preparing project plans, infrastructure development, operation of Pokdarwis (tourism awareness groups) as local tourism communities, determination of market (marketing) strategies, and product development as activities to increase tourism business capacity.